Sosialisasi Program Community Mental Health Nursing di Wilayah Kerja Puskesmas Sako Palembang - Rahmi Imelisa; Riko Sandra Putra (JURNAL PENGABDIAN KADER BANGSA, 2025)
Mental health has now become a global health problem for every country. In this era of globalization and free competition, there is a tendency for mental disorders to increase. According to the World Health Organization Asia Pacific region (WHO SEARO) there are around 450 million people suffering from mental and behavioral disorders worldwide. The importance of the role of family and community in helping improve clients' abilities and preventing relapse is one of the main reasons for the importance of implementing mental nursing care using the Community Mental Health Nursing (CMHN) approach (Keliat, 2011). The aim of this activity is to socialize health workers and the public about CMHN in order to minimize the occurrence of mental health disorders. The method used is socialization of the community Mental Health Nursing program to community leaders, cadres providing outreach to mental health cadres (KKJ) about early detection, home visits and community mobilization as well as health education to the community about CMHN. The results of this activity showed that there were 16 participants in the activity and it went according to the existing plan. The conclusion obtained is that there has been an increase in cadre knowledge after the socialization of the CMHN program and it is hoped that in the future the Sako Health Center will have special cadres for mental health in the community.